Herding, Heterogeneity, and Momentum Trading of Institutional Investors Across Asset Classes - Ben-Horin, Moshe; Kedar-Levy, Haim (Journal of Reviews on Global Economics, 2013)
This paper examines herding, heterogeneity, and momentum trading of institutional investors in Israel across a broad variety of financial assets. While previous studies typically focus on stocks only, we examine herding patterns, heterogeneity, and momentum trading of institutional investors in five asset classes. We find that during the sample period (1/2002 – 12/2011) large investors tended to herd more than medium and small-size investors. In contrast, small investors used momentum trading patterns more than medium and large-size investors. Homogeneity was found among large investors, especially pension funds, and during the first half of the 2000s, when investors purchased corporate bonds at the expense of government bonds. This phenomenon ended upon the beginning of the subprime crisis and against the backdrop of the financial difficulties of the bond issuers. In those years, panicked investors withdrew funds from the most liquid institutions (study funds), while infusing funds to pension and provident funds due to legally binding arrangements. We attribute some of the heterogeneous trading of the institutional investors, to those factors.